TANTANGAN PRODI HUKUM EKONOMI SYARIAH DALAM MENGHADAPI ERA PASAR BEBAS ASEAN (MEA) - Rahayu, Rahayu (Al - Muamalat, 2016)
This article aims to give some suggestions and solutions for academicians, especially for students in majoring Muamalah at Syariah Faculty IAIN Langsa in deal with the era of ASEAN Economic Community or MEA. MEA is mutual agreement to integrate a various ASEAN countries (Indonesia, Singapura, Malaysia, Brunei Darussalam, Thailand, Kamboja, Vietnam, Laos dan Myanmar). Where the countries has a socio-culture background, politic, economic, ideological interest into ASEAN community. As an integrated ASEAN is expected to cooperate in improving efficiency and spuring the economic competitiveness of ASEAN which is indicated through the free flow: goods, services, investment, labor and capital. MEA is a chance and also as a challenge for academicians and for muamalah students in the era of ASEAN Economic Community or MEA.